2015
DOI: 10.1007/s12633-014-9260-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Weathering of Asbestos

Abstract: The process of bioweathering involving natural microbes, natural plants and transgenic animals has proven to be a very efficient and effective tool for detoxifying xenobiotics. The present investigation uses the same tool as a device for detoxifying asbestos, a potent carcinogenic entity. The cellular mechanism of asbestos toxicity to a certain extent, as shown by research, is attributed to its chemical composition particularly the presence of iron in its structure. Many bacteria release iron chelating compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In the U.S., nearly a thousand sites are either contaminated with asbestos-containing materials or naturally occurring asbestos minerals; many are Brownfield sites that are typically left untreated [5], despite imminent health risks to surrounding communities. As the recommended remediation method—soil capping—is cost prohibitive, the potential for alternative cost-effective remediation strategies, including bioremediation, has been explored [713]. However, the bioremediation mechanism and its feasibility in environmental relevant condition is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the U.S., nearly a thousand sites are either contaminated with asbestos-containing materials or naturally occurring asbestos minerals; many are Brownfield sites that are typically left untreated [5], despite imminent health risks to surrounding communities. As the recommended remediation method—soil capping—is cost prohibitive, the potential for alternative cost-effective remediation strategies, including bioremediation, has been explored [713]. However, the bioremediation mechanism and its feasibility in environmental relevant condition is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The same processes could also release iron from asbestos and potentially lower its toxicity. Numerous studies demonstrated that bacteria, lichen, and fungi can degrade asbestos [7–9, 1113, 32, 34, 35] and attributed the degradation to exudates such as organic acids and siderophores. These organic exudates and siderophores can bind ferric and ferrous iron although the exudates have a stronger affinity to ferric iron than ferrous iron [36].…”
Section: Introductionmentioning
confidence: 99%
“…These isolates are able to produce siderophores and were considered to be potential bioremediators for asbestos, as previously demonstrated for Fusarium oxysporum (Daghino et al, 2005;Martino et al, 2004), Verticillium leptobactrum, and Aspergillus fumigatus (Daghino et al, 2008). Bhattacharya et al (2015) showed a decrease in iron content from asbestos by several Rajasthan mine bacterial isolates identified as Gram-positive and -negative bacteria, with two Gram-positive siderophore producers (Bhattacharya et al, 2016b). Bacterial weathering of asbestos has been recently investigated.…”
Section: Introductionmentioning
confidence: 80%
“…Indeed, asbestos is an iron source for various microorganisms. Some studies reported on the one hand, the ability of siderophore-producing organisms to weather asbestos, for example, fungi such as Fusarium oxysporum [81,82], Verticillium leptobactrum, and Aspergillus fumigatus [83], rhizospheric bacteria [14] or Gram-positive bacteria isolates from asbestos mine [13,84]. On the other hand, direct evidence of iron weathering from asbestos by siderophore was shown with deferoxamine [18,85], EDTA [78,85] or citrate [85].…”
Section: Role Of Pyoverdine and Pyochelin In Asbestos Weatheringmentioning
confidence: 99%
“…Indeed, organisms have been isolated from various serpentine sites. Bacteria isolated from asbestos rocks or soil from several Indian mines decrease the iron content of asbestos [13]. Rhizosphere bacteria contribute also to the weathering process in serpentine soil [14].…”
Section: Introductionmentioning
confidence: 99%